Infiltration theory for hydrologic applications - Smith, Roger E. | Smettem, Keith R. J. (American Geophysical Union / Washington, 2002)
Here is your state-of the art quidebook thorugh soil infiltration theory in response to hydrologic problems. By focusing on the theoretical basis of physically based infiltration functions and their application, infiltration theory for hydrologic applications presents an in depth review of current issues and concerns.